Cross-Talk Between Intestinal Microbiota and Host Gene Expression in Gilthead Sea Bream (Sparus aurata) Juveniles: Insights in Fish Feeds for Increased Circularity and Resource Utilization - Naya-Català, Fernando; do Vale Pereira, Gabriella; Piazzon, M. Carla; Fernandes, Ana Margarida; Calduch-Giner, Josep Alvar; Sitjà-Bobadilla, Ariadna; Conceição, Luis E. C.; Pérez-Sánchez, Jaume (Frontiers in Physiology, 2021)
New fish feeds based on processed animal proteins (PAP), insect meal, yeast and microbial biomasses have been used with success in gilthead sea bream. However, some drawback effects on feed conversion and inflammatory systemic markers were reported in different degree with PAP- and NoPAP-based feed formulations. Here, we focused on the effects of control and two experimental diets on the gut mucosal adherent microbiota, and how it correlated with host transcriptomics at local (intestine) and systemic (liver, head kidney) level. The use of tissue-specific PCR-arrays of 93 genes in total rendered 13, 12 and 9 differentially expressed (DE) genes in intestine, liver and head kidney, respectively. Illumina sequencing of gut microbiota yielded a mean of 125,350 reads per sample, assigned to 1,281 OTUs. The bacterial richness and alpha diversity were lower in fish fed the PAP diet, and discriminant analysis displayed 135 OTUs driving the separation between groups with 43 taxa correlating with 27 DE genes. The highest expression of intestinal pcna and alpi was achieved in PAP fish with intermediate values in NoPAP, being the pro-inflammatory action of alpi associated with the presence of Psychrobacter piscatorii. The intestinal muc13 was down-regulated in NoPAP fish, being this gene negatively correlated with anaerobic (Chloroflexi and Anoxybacillus) and metal-reducing (Pelosinus and Psychrosinus) bacteria. Other inflammatory markers (igm, il8, tnfα) were up-regulated in PAP fish, positively correlating the intestinal igm with the inflammasome activator Escherichia/Shigella, whereas the systemic expression of il8 and tnfα was negatively correlated with the Bacilli class in PAP fish and positively with Paracoccus yeei in NoPAP fish. Overall changes in the expression pattern of il10, galectins (lgals1, lgals8) and toll-like receptors (tlr2, tlr5, tlr9) reinforced the anti-inflammatory profile of fish fed the NoPAP diet, being these gene markers associated with a wide-range of OTUs. A gut microbiota-liver axis was also established, linking the microbial generation of short chain fatty acids with the fueling of scd1- and elovl6-mediated lipogenesis. In summary, by correlating microbiome with host gene expression, we offer new insights in the evaluation of fish diets promoting gut and metabolism homeostasis, and ultimately the health of farmed fish.